An efficient superframe structure with optimal bandwidth utilization and reduced delay for internet of things based wireless sensor networks - Khan, Sangrez; Alvi, Ahmad Naseem; Javed, Muhammad Awais; Roh, Byeong Hee; Ali, Jehad (Sensors (Switzerland), 2020)
Internet of Things (IoT) is a promising technology that uses wireless sensor networks to enable data collection, monitoring, and transmission from the physical devices to the Internet. Due to its potential large scale usage, efficient routing and Medium Access Control (MAC) techniques are vital to meet various application requirements. Most of the IoT applications need low data rate and low powered wireless transmissions and IEEE 802.15.4 standard is mostly used in this regard which offers superframe structure at the MAC layer. However, for IoT applications where nodes have adaptive data traffic, the standard has some limitations such as bandwidth wastage and latency. In this paper, a new superframe structure is proposed that is backward compatible with the existing parameters of the standard. The proposed superframe overcomes limitations of the standard by fine-tuning its superframe structure and squeezing the size of its contention-free slots. Thus, the proposed superframe adjusts its duty cycle according to the traffic requirements and accommodates more nodes in a superframe structure. The analytical results show that our proposed superframe structure has almost 50% less delay, accommodate more nodes and has better link utilization in a superframe as compared to the IEEE 802.15.4 standard.
Keywords: Application requirements; Backward compatible; IEEE 802.15.4 standards; Internet of Things (IOT); Medium access control(MAC); Optimal bandwidths; Traffic requirements; Wireless transmissions; Internet of Things; Superframe structure; Wireless sensor networks